Mineral Resources and Economic Development Of Nepal (शोधसुधा Shodh Sudha, 2024)
Mineral resource is the mineral deposit consisting of useful concentration that may or may not exceed economic cost for obtaining the valuable minerals. The information was collected through Secondary data. The data collected from different sources have been analyzed on the basis of these classification using both analytical and descriptive methods. The technological process, the needs of the economy and prices in the market, depends on whether and when the rock/mineral becomes raw material. The study aims to explore Mineral resources is important for economic development of  Nepal. Mineral Resources has great importance for  improvement in the economic status household.  This research also shows the problems of mineral Resources. Mineral Resources has  positive change in the overall socio- economic status  and overall economic development  of  Nepal.